A COMUNICAÇÃO ENQUANTO ARTEFATO TECNOLÓGICO: POSSIBILIDADES E ANGULAÇÕES - PALAMEDI, FABIO DOS SANTOS (2018)
This research is motivated by the question: what is technology and what is its relation to communication? There are many approaches to technology, but generally in paper support, or in a secondary way in communication studies, provided by the most varied technologies available in societies. For this reason, this research mapped the historical concepts that delineated and determined the meaning in history, the philosophical aspect of the questioning about technology, and a structural analysis of the concept that occurred throughout the studies dedicated to the subject. In addition, the same methodological clipping is also applied to questions related to information, as well as a parallel, contrasting these clipping with what traditional theories of communication place as an object. As a result, the research carried out specifically in the field of Communication was integrally linked to the references used in national journals and annals, considering the entire period of existence of each of the journals, totaling a total of 13,715 articles in 44 Qualis A1 and B1 journals. The results indicate that there is no direct approach of a scope delimitation to technology in such publications, in contrast to reflections and research related to generalist technologies. From the same universe, it was found that only 4% of all indexed articles address these technologies, and only one article addresses a more comprehensive concept. Therefore, the study showed that there is no such approach related to the concept of communication technology, and there is no clear relationship between technology and communication.